2016
DOI: 10.3389/fnmol.2016.00014
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of the 1H-MRS Metabolite Spectrum in Autism Spectrum Disorder

Abstract: Neuroimaging studies of neuropsychiatric behavior biomarkers across spectrum disorders are typically based on diagnosis, thus failing to account for the heterogeneity of multi-dimensional spectrum disorders such as autism (ASD). Control group trait phenotypes are also seldom reported. Proton magnetic resonance spectroscopy (1H-MRS) measures the abundance of neurochemicals such as neurotransmitters and metabolites and hence can probe disorder phenotypes at clinical and sub-clinical levels. This detailed review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
93
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 134 publications
7
93
2
2
Order By: Relevance
“…Another study detected reduced neuronal firing in iPSCderived neurons of eight individuals with idiopathic ASD (Marchetto et al, 2017) and detected a correlation of reduced network complexity to behavioral and cognitive phenotype of the donors (Amatya et al, 2019). Moreover, reduced GABA concentration, as seen in the ASDCASK_SS brain was reported in groups of children with ASD (Ford and Crewther, 2016).…”
Section: Cask-related Disorders Have Emerged As An Important Genetic mentioning
confidence: 92%
“…Another study detected reduced neuronal firing in iPSCderived neurons of eight individuals with idiopathic ASD (Marchetto et al, 2017) and detected a correlation of reduced network complexity to behavioral and cognitive phenotype of the donors (Amatya et al, 2019). Moreover, reduced GABA concentration, as seen in the ASDCASK_SS brain was reported in groups of children with ASD (Ford and Crewther, 2016).…”
Section: Cask-related Disorders Have Emerged As An Important Genetic mentioning
confidence: 92%
“…106 A systematic review found reduced absolute levels of subcortical N-acetylaspartate and creatine along with phosphocreatine. 107 Other notable findings were increased creatine, phosphocreatine, glutamate, N-acetylaspartate, and myoinositol in the cortical white matter. In addition, the gray matter had elevated creatine, phosphocreatine, glutamate, N-acetylaspartate, and choline.…”
Section: High-angular-resolution Diffusion Imagingmentioning
confidence: 97%
“…A meta‐analysis of 22 studies with a total of 632 typically developing individuals and 844 individuals with ASD found significantly lower N ‐acetylaspartate levels in the frontal regions of the ASD group . A systematic review found reduced absolute levels of subcortical N ‐acetylaspartate and creatine along with phosphocreatine . Other notable findings were increased creatine, phosphocreatine, glutamate, N ‐acetylaspartate, and myoinositol in the cortical white matter.…”
Section: Neurobiology Of Asdmentioning
confidence: 99%
See 2 more Smart Citations